The 2020 M6.4 Jiashi Earthquake: An Event that Occurred Under the Décollement on the Kaping Fold-and-Thrust Belt in the Southwestern Tien Shan Mountains, China - Yao, Qi; Yang, Wen; Jiang, Xianghua; Guo, Yanshuang; Liu, Jie; Zhang, Yongxian; Wang, Hui; Ren, Jing; Yu, Cheng; Yue, Chong; Zhao, Jing (Frontiers in Earth Science, 2021)
The 2020 Jiashi M6.4 earthquake occurred in the Kaping fold-and-thrust belt, a major south-verging active thin-skin system in the southwestern Chinese Tien Shan Mountain, north of the Tarim Basin. Within 50 km from the epicentral area, seismic hazard is high, as suggested by the occurrence of the 1902 Mw 7.7 Artux (Kashgar) earthquake and 1997 Jiashi strong earthquake swarm. The seismogenic structure responsible for the 2020 event is not well constrained and is a subject of debate. We relocated the 2020 Jiashi earthquake sequence and assessed the relocation uncertainties, using eight seismic velocity models and based on detailed local and regional subcrustal structures from seismic profiles. Then we compared the temporal variation in the Gutenberg-Richter b-values of the 2020 sequence with those of the 1997, 1998, and 2003 earthquake sequences. Our results show that most events cluster at depths greater than 10 km, suggesting that the events most likely occurred beneath the décollement and inside the Tarim Craton. The spatiotemporal evolution of the sequence suggests that two groups of structures at depth were involved in the 2020 sequences: NW-SE-trending lateral strike-slip faults and E-W-trending reverse faults. The b-values of the 2020 sequence exhibits relatively stable temporal evolution, unlike those of the multi-shock sequence that occurred inside the Tarim Craton. It indicates that the 2020 sequence perhaps was influenced by the stress interaction with the 10-km thick overlying strata. Our study provides a new perspective on the seismogenic structure of the earthquakes that occurred because of reactivation of ancient structures developed in a stable craton.